Orientasi Nilai Budaya Masyarakat Nias dalam Maena pada Upacara Falöwa - Titian Berkat Gea (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
This study aims to describe the orientation of Nias cultural values ​​in the lyrics of the maena at the falöwa traditional ceremony in Gunungsitoli. The research was conducted using a qualitative method with an anthropolinguistic approach. The data in this study is a snippet of the lyrics of the maena at the traditional falöwa (wedding) ceremony, either spoken orally or a collection of written lyrics. Primary data sources are the results of interviews with informants and recordings of playing. The secondary data source is the maena lyric text in the book "Maena Nias – Means of Delivering Messages and Life Stories of the Nias Society," published by the Nias Heritage Museum, 2018. Data were collected using observation and interview methods. The observation method is carried out using the tapping and nonparticipation and the recording techniques as further techniques. The interview method uses direct interview techniques. Then, the data were analyzed in stages: (1) data reduction, (2) data presentation, and (3) making conclusions/verification. In the analysis process, the researcher also validated the data by applying data triangulation. The triangulation used in this study is source triangulation. The study results concluded that, first, the society of Nias interprets the nature of life as something that needs to be fought for. Second, the society of Nias views that the nature of the work can increase the position and honor of humans in their environment. Third, Nias society view that humans are influenced by space and time. Fourth, Nias society views the importance of harmonious relations between humans and their natural surroundings. Fifth, Nias society upholds human relations with each other.